2012
DOI: 10.1021/jf2043949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orange Juice’s Processing on the Color, Particle Size, and Bioaccessibility of Carotenoids

Abstract: This study was aimed at assessing the differences between industrially processed and hand-squeezed orange juices (OJs) in relation to their color, particle size, carotenoid content, and carotenoid bioaccessibility. Specifically, industrial samples of fresh squeezed OJs after the finishing steps (FISO) and the same OJs after pasteurization (PISO), as well as hand-squeezed OJs (HSO) were studied. The results showed that the HSO and PISO were different (p < 0.05) in terms of color (darker and more reddish vs brig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
72
3
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 32 publications
15
72
3
2
Order By: Relevance
“…In general, these results, agree with results published previously by Fernández-Vázquez et al [32], suggesting that no clear preferences for any colour was observed but that there are subsections of the population that show different preferences for OJ colour. They found that consumer clusters did not differ in terms of gender, age, or consumption habits indicating that these variables did not influence colour preference patterns.…”
Section: Expected Liking Vs Actual Likingsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, these results, agree with results published previously by Fernández-Vázquez et al [32], suggesting that no clear preferences for any colour was observed but that there are subsections of the population that show different preferences for OJ colour. They found that consumer clusters did not differ in terms of gender, age, or consumption habits indicating that these variables did not influence colour preference patterns.…”
Section: Expected Liking Vs Actual Likingsupporting
confidence: 93%
“…This is likely to relate to the association of more reddish hues in a freshly squeezed OJ indicating superior quality [31][32][33]. However, there were no significant differences in actual liking between any of the samples, which is in accordance with Tepper [25], who concluded that slight green colour variation reduced consumer acceptance regarding colour, but had little influence on overall liking.…”
Section: Influence Of Colour On Expected and Actual Likingsupporting
confidence: 71%
“…(all-E)-Lutein (peak 12) and (all-E)-zeaxanthin (peak 14) have the same chemical formula (C 40 + . This fact also affects the UV-Vis features and elution of these carotenoids, allowing their unequivocally identification.…”
Section: Methods Validationmentioning
confidence: 99%
“…38,39 In a recent study, violaxanthin, antheraxanthin, and their geometrical isomers, as well as luteoxanthin and mutatoxanthin were found as the major carotenoids in ultrafrozen juice from Valencia late orange. 40 The developed method was also applied to freeze-dried mango, and concerning its carotenoid composition, (all-E)-violaxanthin was the major compound (37%), followed by (all-E)-β-carotene (24%) and (9Z)-violaxanthin (23%). Other minor compounds, such as β-carotene cis-isomers and neoxanthin, were also detected (Table 6).…”
Section: Methods Validationmentioning
confidence: 99%
“…Enhancing cloud stability without increasing the viscosity of the product is one of the main challenges in citrus juice industry (Galant, Widmer, Luzio, & Cameron, 2014). There is evidence in orange juice as in other puré ed products, of an inverse relationship between particle size of the food matrix estimated by laser diffraction analysis and carotenoid relative accessibility, expressed as percentage of total carotenoids released in solubilized form after simulated digestion trials (Stinco et al, 2012). A different distribution of carotenoids between serum and cloud particles seems to play a role also in discoloration phenomena during processing of blood orange juices (Arena, Fallico, & Maccarone, 2000) along with thermal and enzymatic degradations of anthocyanin compounds (Cisse, Vaillant, Acosta, Dhuique-Mayer, & Dornier, 2009;Rapisarda et al, 2001).…”
Section: Introductionmentioning
confidence: 99%